Exclusive Legal Personality of States in East Asia and the Legacy of Bandung Pragmatism - Toyoda, Tetsuya (UI Scholars Hub, 2024)
One of the significance of the Bandung Conference was the down-to-earth realism. The People's Republic of China (PRC) was among the major promoters of the conference, despite its mostly unrecognized status in the international community. The exclusive legal personality is the central tenet of the modern system of international law, where non-sovereign entities are strictly discriminated against sovereign ones. The introduction of international law in East Asia in the late-nineteenth century was particularly troublesome with the eventual denial of legal personality of semi-sovereign entities, such as the kingdom of Lew Chew, the Joseon dynasty, or the government of Tibet. East Asia today still sees the co-existence of mutually non-recognizing entities that are PRC and the Republic of China (ROC), as well as the Republic of Korea (ROK) and the Democratic People's Republic of Korea (DPRK). To deal with such a reality, we have established the practice of regional security dialogue where the DPRK has been included since 2000. We have the Asia-Pacific Economic Cooperation (APEC) forum, where both the PRC and ROC have been included in since 1991, leading to the inclusion of two Chinas in the WTO in 2001. The strict distinction between sovereign and non- sovereign entities is only a modern phenomenon, even in Western Europe, where the concept started to develop in the 17th century. The legacy of the Bandung Conference may be reappraised with its sense of pragmatism and be a starter for a postmodern and non-Western conceptualization and configuration of a community of international law.